Synergistic upconversion and molecular imprinting in flame-made Yb/Nd co-doped TiO2 for targeted photocatalytic degradation of tetracycline in complex water - Xinhao Meng; Shuohan Wu; Zhijun Yang; Heran Zhang; Zhengliang Bian; Dongliang Zhang; Shuning Xiao; Yanjie Hu; Ying Li; Wei Bi (Environmental Research, 2026)

Reaction-induced Ni/C working interface enables process-intensified microwave-plasma valorization of polyolefin-rich plastic wastes into H2-rich gas and graphitized carbon nanomaterials - Hao Zheng; Yang Xu; Jiabin Geng; Chengcheng Ma; Yingchun Miao; Shuning Xiao (Journal of Environmental Chemical Engineering, 2026)

Measuring and modelling of seed-applied pesticides during soybean emergence - Yang Liu; Xiangshuai Li; Fangkui Zhao; Huizhu Yuan; Xiaojing Yan; Shuning Chen; Daibin Yang (Plant and Soil, 2026)

Fluctuations in groundwater inflow induced by periodic fracturing of overlying strata with mining - Shuning Dong; Zhenfang Zhou; Yang Dong; Qiang Ji; Jiankun Xue; Tiantian Wang; Yutong Wang; Le Han; Peiqiang Gao; Shenghu Luo; Yingying Yao (Bulletin of Engineering Geology and the Environment, 2026)

Functional identity of typhoon-derived green litter overrides functional dissimilarity in reshaping litter faunal feeding guilds in a subtropical forest - Shuning Ma; Lifeng Wang; Qingjun Ma; Ajuan Zhang; Rui Cao; Zhuang Wang; Qin Wang; Mei Qin; Wanqin Yang (Plant and Soil, 2026)

Relative quantitative data of cosmetics consumption: An online survey in Guangzhou, China - Junfeng Deng; Zhen Wu; Xiaodan Lu; Xiaoyu Xian; Shixiong Zheng; Yunying Mo; Tianyang Liu; Siyu Sun; Shihan Huang; Ye Hong; Xingyu Yu; Aliya Yijiati; et al. (Regulatory Toxicology and Pharmacology, 2026)

Coarse Woody Debris Maintains Two Distinct and Interrelated Detrital Food Webs in Forest Ecosystems - Zhihui Wang; Yuchen Lu; Shuning Ma; Benjuan Liu; Rui Cao; Lifeng Wang; Yong Zhang; Wanqin Yang (Ecosystems, 2026)

Classification and Evaluation of a Shale Oil Reservoir in the Qingshankou Formation in the Southern Songliao Basin, NE China - Guofeng Wang; Dawei Zhang; Liang Yang; Yongqing Zhang; Junling He; Jilin Xing; Jun Jiang; Jijun Li; Shuning Zhang; Chenxu Yan; Hang You; Ketao Zheng; et al. (Journal of Earth Science, 2026)

Microwave-triggered plasma catalysis over Cu/CuOx wires: Synergistic CO2 reduction via enhanced discharge and dynamic oxygen vacancies - Shuning Xiao; Yang Xu; Haotong Ma; Xiuwen Zhao; Hao Zheng; Shuo Wang; Zhanshuo Tao; Hexing Li (Chemical Engineering Journal, 2026)

Binding of neonicotinoid compounds to Apis mellifera chemosensory protein 3 (AmelCSP3): Insight into the molecular toxicity of compounds with both risk and potential - Shiyu Li; Xiangshuai Li; Yang Liu; Fangkui Zhao; Daibin Yang; Li Cui; Shuning Chen; Huizhu Yuan; Xiaojing Yan (Pesticide Biochemistry and Physiology, 2025)

Interactions in starch-lipid complex systems improve 3D printing accuracy and form resistant starch structures: Based on complex properties and molecular simulations - Yanru Bao; Shu Ma; Shuning Yuan; Yu Hu; Tao Yang; Hao Jiang (Food Chemistry, 2025)

Differential Effects of Murine Stroke Models on Dopaminergic Neurons, Glial Responses, and Neurobehavioral Outcomes - Sidra Tabassum; Heng Hu; Silin Wu; Shuning Huang; Bosco Seong Kyu Yang; Chang-Hun Lee; Aaron W. Gusdon; Xuefang S. Ren (Translational Stroke Research, 2025)

Dopamine-functionalized chondroitin sulfate/gelatin-based composite hydrogels for enhancing wound healing and bone regeneration - Jian Yang; Jiale Jin; Haojie Yu; Yun Wang; Li Wang; Xiaowei Liu; Dongyu Wang; Yudi Huang; Chenguang Ouyang; Yu Wang; Yichuan Hong; Shuning Ren; et al. (Carbohydrate Polymers, 2025)

A resonance energy transfer electrochemiluminescence sensor based on the synergistic effect of luminol@β-cyclodextrin and Ni-MOF@Pt NPs for the oxytetracycline detection - Li Tian; Shuning Yang; Guangping Ma; Pengfei Han; Hanyue Jiang; Wenzhuo Wang; Juan Lu (Food Chemistry, 2025)

Dual-site Langmuir-Hinshelwood mechanism in ZnCr-LDH/NH2-UIO66 heterojunction for efficient photocatalytic NO oxidation - Jing Guo; Haotong Ma; Huan Shang; Wenchao Wang; Ruiyi Yang; Shuo Wang; Yingchun Miao; David Lee Phillips; Guisheng Li; Shuning Xiao (Journal of Hazardous Materials, 2025)

Production of fucose-rich exopolysaccharides by UV-mutated Enterobacter: Optimization, structural characterization and functional properties - Zhemin Li; Shuning Ren; Xiufang Bi; Dan Shu; Di Luo; Jie Yang; Xin Li (Food Bioscience, 2025)

Solid-state electrochemiluminescence sensor based on TiO2@CdSe and Ru(bpy)32+@Ag NPs for ultrasensitive detection of malathion - Huiling Li; Li Tian; Shuning Yang; Chao Li; Ruidan Li; Yujia Song; Yanjia Guo; Xuwen Li (Food Chemistry, 2025)

Towering sustainability: Unraveling the complex effects of skyscrapers on urban resilience - Yihua Yu; Caili Yang; Qingsha Hu; Shuning Kong (Environmental Impact Assessment Review, 2024)

Associations of Plasma Lipidomic Profiles with Uric Acid and Hyperuricemia Risk in Middle-Aged and Elderly Chinese - Wanhui Kang; Xinming Xu; Xiaowei Yang; Qingqing Wu; Shuning Li; Keran Gao; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2024)
Little is known about the links of disturbed lipid metabolism with hyperuricemia (HUA). We aimed to investigate the associations of lipidomic profiles with uric acid (UA)/HUA and their modifying factors in middle-aged and elderly Chinese. A total of 350 lipids were quantified in 2247 community-based Chinese aged 50–70 years by high-coverage targeted lipidomics. HUA was defined by plasma UA > 420 μmol/L in men or > 360 μmol/L in women. The prevalence of HUA in this population was 10.4%. After multivariable adjustment including BMI and lifestyle, 123 lipids were significantly associated with UA, predominantly glycerolipids (GLs) and glycerophospholipids (GPs). Specifically, diacylglycerol [DAG (16:0/22:5), DAG (16:0/22:6), DAG (18:1/20:5), DAG (18:1/22:6)], phosphatidylcholine [PC (16:0/20:5)), and triacylglycerol (TAG (53:0)] were the most significant lipid signatures positively associated with HUA risk, while lysophosphatidylcholine (LPC (20:2)) was inversely associated with HUA risk ( p < 0.05). Network analysis also showed a positive association between TAGs/PCs/DAGs contained module and HUA risk ( p < 0.01). Notably, HUA-related lipids were associated with de novo lipogenesis fatty acids, especially 16:1n-7 (Spearman correlation coefficients = 0.32–0.41, p < 0.001). Reduced rank regression showed that increased aquatic products intake was correlated to elevated HUA risk and HUA-associated lipids; while high dairy consumption was correlated with low level of HUA-associated lipids (|factor loadings| ≥ 0.2). Moreover, mediation analyses suggested that the lipid-HUA associations were partially mediated by retinol-binding protein 4 (RBP4, mediation proportion 5–14%), an adipokine linked with dyslipidemia and insulin resistance. In conclusion, disturbed specific metabolisms of GLs and GPs were associated with high prevalent HUA, partially mediated by RBP4 and/or influenced by certain dietary factors.

Utilization of γ-polyglutamic acid/pectin hydrogel with 1-MCP on the apricot storage - Shuning Yang; Jinfeng Zhang; Xiaopei Hu; Suhong Li; Tuoping Li (Journal of Stored Products Research, 2024)

An all-in-one FeOx-rGO sponge fabricated by solid-phase microwave thermal shock for water evaporation and purification - Youkun Sun; Xiuwen Zhao; Xueling Song; Jinchen Fan; Junhe Yang; Yingchun Miao; Shuning Xiao (Journal of Environmental Sciences, 2024)

An electrochemiluminescence sensor based on the CNTs and CdSe@ZnSe for determination of melamine in milk samples - Qian Wu; Li Tian; Xiangyu Shan; Huiling Li; Shuning Yang; Chao Li; Juan Lu (Food Chemistry, 2024)

Coarse woody debris and litter layer exert differential roles in nursing soil fungal communities across a subalpine forest successional series - Zhihui Wang; Fei Li; Jianfeng Hou; Xuqing Li; Rui Cao; Yurui Jiang; Yuchen Lu; Shuning Ma; Wanqin Yang (Acta Oecologica, 2023)

Intelligent real-time identification technology of stratum characteristics during slurry TBM tunneling - Yingran Fang; Xinggao Li; Hongzhi Liu; Shuning Hao; Yang Yi; Yidong Guo; Hanyuan Li (Tunnelling and Underground Space Technology, 2023)

Impacts of core parameters on the capability of Cf-252 production in an MSR - Chunyan Zou; Chenggang Yu; Jun Zhou; Shuning Chen; Shaopeng Xia; Yang Zou; Xiangzhou Cai; Jianhui Wu; Jingen Chen (Annals of Nuclear Energy, 2023)

Electrospun nanofibres containing Zn-MOF for electrochemiluminescent determination of fenpropathrin residues in fruit juices - Zhuo Sun; Juan Lu; Xin Zhang; Xiangyu Shan; Qian Wu; Chao Li; Huiling Li; Shuning Yang; Li Tian (Food Chemistry, 2023)

Photo-sonodynamic therapy mediated with OLI_NPs to induce HPV16E7-specific immune response and inhibit cervical cancer in a Tc-1-grafted murine model - Guangzong Zhao; Shuning Chen; Jiao Zheng; Chenyang Li; Xiaowen Zhong; Yang Cao; Yue Zheng; Jiangchuan Sun; Shenyin Zhu; Shufang Chang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Identifying spatial relations of industrial carbon emissions among provinces of China: evidence from unsupervised clustering algorithms - Shuning Liu; Chaojun Yang; Liju Liu (Environmental Science and Pollution Research, 2022)

Dynamic Characteristics of Water Inflow from a Coal Mine’s Roof Aquifer - Zhenfang Zhou; Shuning Dong; Hao Wang; Dewu Jin; Xiaodong Wang; Yang Dong; Shi Chen; Debin Li; Xingling Dong; Hongbo Shang (Mine Water and the Environment, 2022)

Directed evolution of the PobR allosteric transcription factor to generate a biosensor for 4-hydroxymandelic acid - YaoYao Liang; Juan Luo; Chenhao Yang; Shuning Guo; Bowen Zhang; Fengqianrui Chen; Kairui Su; Yulong Zhang; Yi Dong; Zhihao Wang; Hongda Fu; Guangchao Sui; et al. (World Journal of Microbiology and Biotechnology, 2022)

The Water Resisting Properties of the Top Portion of the Ordovician Limestone Aquifer in the North China Coalfield - Hao Wang; Shuning Dong; Rui Chai; Wei Qiao; Jian Yang; Ji Liu; Linsheng Zhou; Zhenfang Zhou; Zhaoxing Liu; Hongbo Shang (Mine Water and the Environment, 2021)

Mine Water Source Discrimination Based on Hydrogeochemical Characteristics in the Northern Ordos Basin, China - Jian Yang; Shuning Dong; Hao Wang; Guoqing Li; Tiantian Wang; Qiangmin Wang (Mine Water and the Environment, 2021)

Effects of Groundwater Table Decline on Vegetation Transpiration in an Arid Mining Area: A Case Study of the Yushen Mining Area, Shaanxi Province, China - Qiangmin Wang; Shuning Dong; Hao Wang; Jian Yang; Chunhu Zhao; Xingling Dong; Tiantian Wang (Mine Water and the Environment, 2020)

Radiation-Induced Bystander Effects in A549 Cells Exposed to 6 MV X-rays - Shuning Yang; Jing Xu; Weixian Shao; Chong Geng; Jia Li; Feng Guo; Hui Miao; Wenbin Shen; Tao Ye; Yazhou Liu; Haiting Xu; Xuguang Zhang (Cell Biochemistry and Biophysics, 2015)